2016
DOI: 10.1259/bjr.20150502
|View full text |Cite
|
Sign up to set email alerts
|

Choline-to-N-acetyl aspartate and lipids-lactate-to-creatine ratios together with age assemble a significant Cox's proportional-hazards regression model for prediction of survival in high-grade gliomas

Abstract: S. Choline-to-N-acetyl aspartate and lipids-lactate-tocreatine ratios together with age assemble a significant Cox's proportional-hazards regression model for prediction of survival in high-grade gliomas. Br J Radiol 2016; 89: 20150502. FULL PAPERCholine-to-N-acetyl aspartate and lipids-lactate-to-creatine ratios together with age assemble a significant Cox's proportional-hazards regression model for prediction of survival in high-grade gliomas Objective: A long-lasting concern has prevailed for the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Nevertheless, contamination of the lactate peak with signals of lipids cannot be completely avoided, and the amount remains unclear. Previous studies described a correlation of the progression-free survival with the lactate/creatine ratio [ 15 , 16 ], or the distribution of metabolites with tumor subtypes [ 17 ]. Despite the comparatively low number of patients in this study, the relative changes in the lactate concentrations among the different regions were significant.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, contamination of the lactate peak with signals of lipids cannot be completely avoided, and the amount remains unclear. Previous studies described a correlation of the progression-free survival with the lactate/creatine ratio [ 15 , 16 ], or the distribution of metabolites with tumor subtypes [ 17 ]. Despite the comparatively low number of patients in this study, the relative changes in the lactate concentrations among the different regions were significant.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent studies have shown the importance of Cho/NAA and LL/Cr ratios in assembling significant survival models in glioblastoma. 10 The use of DTI allows diffusion directionality to be quantified as different DTI-derived metrics 21 ; it yields ultrastructural information on cellular density and properties of the extracellular matrix. 22 In 2006, Pena et al expressed that it was not completely understood the magnitudes and associations among DTI measurements observed in the evaluation of brain tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The results might be compared with previously published models. 10 To simplify the discussion of our findings, we grouped them into four sections:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance spectroscopy (MRS) grant in vivo analysis of cerebral metabolites that establish chemical content in some brain regions, some of the metabolites more frequently studied is choline, N-acetyl aspartate (NAA), creatine and glutamate (Glu) [60]. Although the most common use of MRS has been in the evaluation of glioblastoma's survival [61], and epilepsy [62], recent applications of the MRS for environmental diseases have identified neurodevelopment variations due to prenatal exposure [4]. Studies about prenatal exposition to environmental pollution and the exposition during the first year of life are essential because of the importance of brain development during this time [63].…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%